Mecanismos envolvidos na ação antinociceptiva e antiinflamatória do flavonóide miricitrina: estudos in vivo e in vitro" - Meotti, Flavia Carla (2006)
The intake of flavonoids is closely associated with diminished risks of cancer, atherosclerosis and other chronic inflammation disturbance related. These compounds are described, mainly, by their anti-inflammatory and antioxidant activities. Myricitrin is a flavonoid that inhibits protein kinases and NO production. Therefore, the research of the mechanisms by which these compounds exerts their effects is extremely interesting for the therapeutic application. In this study, the antinociceptive and anti-inflammatory activities of myricitrin as well as its mechanisms of action were investigated. The systemic (p.o. or i.p.) and central (i.c.v. or i.t.) administration of myricitrin reduced in a dose-dependent manner the visceral pain induced by acetic acid. The i.p. treatment with myricitrin also prevented nociception induced by i.pl. injection of glutamate, capsaicin, PMA and by i.t. injection of glutamate, SP, TNF-α and IL-1β in mice. In addition, myricitrin treatment inhibited mechanical hyperalgesia induced by BK, but not that induced by epinephrine or PGE2 in rats. Western blot analysis revealed that myricitrin treatment fully prevented PKCα and PKCε activation by PMA in mice hindpaw. The antinociception caused by myricitrin in the acetic acid test was significantly reverted by Gi/o protein inactivation (pertussis toxin treatment); treatment with ATPgated K+ channel blocker (glibenclamide), CaCl2 and L-arginine (NO precursor) administration. However, myricitrin-induced antinociception was modified neither by antagonist opioid (naloxone) nor by neonatal capsaicin treatment (which depletes 80% of unmyelinated C fibers). In addition, myricitrin effects were not associated with sedative and muscle-relaxant action. In vitro assays using slices of cerebral cortex of rats revealed that myricitrin inhibited calcium transport in a depolarizing condition; however, at higher concentration, it inhibited calcium transport also in a non-depolarizing condition. Myricitrin increased nociceptive threshold in mechanical allodynia induced by both partial sciatic nerve ligation (neuropathic pain) and FCA i.pl. injection (inflammatory chronic pain). This same treatment decreased paw edema, morphological alterations and MPO activity (proinflammatory enzyme) in FCA hindpaw. On the other hand, it did not reduce neutrophils migration to inflammation site. Myricitrin produced potent antioxidant activity when assessed by Fe2+-induced lipid peroxidation. In conclusion, the present study showed that myricitrin exhibits antinociceptive and anti-inflammatory activity when analyzed in acute and chronic models of nociception. The mechanisms involved in the myricitrin beneficial effects included Gi/o protein activation, ATP- gated K+ channels opening, inhibition of PKC, NO synthesis, wedged of Ca2+ transport, inhibition of MPO activity and scavenger action.